The Kerygma and the Cuckoo's Nest - Slater, Peter (Scottish journal of theology, 1978)
Influenged by Tillich's so-called method of correlation, theologians in recent decades have been inclined to approach existential situations as if they simply raised questions to which the dogmatic tradition provided answers. Accordingly, in my teaching for example, I have often read Camus's The Plague together with Buber's I and Thou, Tillich's The Courage To Be with Brecht's Mother Courage and so on. However, the effect of such correlations has, as often as not, been to set the questions moving in the other direction. The traditional ‘answers’ of theologians have been challenged by the existential concerns of the secular writers. In particular the very raison d'être of theology, the articulation of the transcendent presence of God in the world, has become problematical.Granted that Buber's I-You relationship correlates with Camus's portrayals of authenticity, for instance, why do we need to mention Buber's ‘Eternal You’? Can we even make sense of such talk? Granted that Tillich's types of anxiety correlate with his sense of faithful courage, must his affirmation of life in spite of the negativities of existence be ontologically rooted in some ‘Ground of Being’? As we ponder such questions the existential contexts discussed seem to have evaporated all content from the theological answers.